Bladder Neck Closure in Children: Long-Term Results and Consequences - Hernandez-Martin, Sara; Lopez-Pereira, Pedro; Lopez-Fernandez, Sergio; Ortiz, Rubén; Marcos, Mercedes; Lobato, Roberto; Martinez-Urrutia, Maria Jose; Jaureguizar, Enrique (European Journal of Pediatric Surgery, 2015)
Aim Only few studies have gathered information on the long-term outcomes of children undergoing bladder neck closure (BNC). In the present study, we analyze the long-term results and consequences in this population.Patients and Methods The medical records of 20 patients (12 males and 8 females), who underwent BNC after several failed procedures to improve urinary incontinence were revised. Exstrophy complex was the underlying diagnose in all the cases: bladder exstrophy in 15 and cloacal exstrophy in 5. The median age of the patients at the time of surgery was 11.5 years (range 4–19 years). Previous surgeries were bladder neck reconstruction in 14 patients, bladder neck injection in 4 patients, and previous BNC in 1 patient. Overall 17 patients had concomitant bladder augmentation. The catheterizable stoma was made with appendix in 14, bowel in 3, and ureter in 3. The nine male patients aged > 18 years at the time of this study received a questionnaire with specific questions on erections, orgasm, and details of ejaculation and were also asked to provide a semen sample.Results The median follow-up was 10 years (range 2–17 years) and median patient age was 21 years (range 13–32 years). Urinary continence was achieved initially in 16 patients (80%); 4 had a bladder neck fistula, 3 of them underwent surgical revision and achieved dryness. Long-term complications were: bladder stones (eight patients); stomal problems (four stenosis and three leaks); bladder perforation (two patients), and orchitis (one patient). All patients above the age of 18 years reported erections and orgasms although two had medium erectile dysfunction. The ejaculate volume was reported as normal in five, scarce in three, and absent in one, with slow ejection in seven. Only four supplied semen samples and only two showed normal values.Conclusions BNC is an effective approach to incontinence when other procedures have failed. In the long term, the most frequent complications are those related with catheterizable stoma and stones. The high incidence report of a low fertility index and erectile dysfunction meant further study in a larger cohort.
Keywords: urinary incontinence; bladder exstrophy; bladder neck closure; erectile dysfunction; continent conduit; catheterization